Workshop on professionalism and professional identity formation for newly recruited faculty at a healthcare university: lessons learnt - Pandya, Himanshu; Varma, Jagdish; Ghosh, Sarmistha; Kumar, Dinesh; Prabhakaran, Anusha; Prakash, R. Harihara (Frontiers in Medicine, 2025)
BackgroundHealthcare is inherently human-centered, and professionalism is crucial for improving healthcare systems. Traditionally developed through role modeling, professionalism now necessitates explicit teaching. Despite the inclusion of professionalism-related competencies by Indian regulatory bodies in medicine and nursing, its structured teaching remains limited. To address this, we introduced concepts of Professionalism and Professional Identity Formation (PIF) to newly joined faculty at our university, following established frameworks. This report details the workshop process and key lessons learned.MethodsA six-member core faculty team with expertise in health professions education conducted a daylong workshop. The morning session focused on contemporary perspectives on professionalism, while the afternoon session addressed PIF. Anonymous post-session feedback was collected via Google Forms, with quantitative responses rated on a five-point Likert scale and qualitative feedback analyzed using Braun and Clarke’s six-phase thematic analysis.ResultsThree workshops were held in June 2024 for faculty who had joined over the past 2 years. Attendance across the three sessions was 25, 23, and 24 participants, respectively, from medicine, physiotherapy, nursing, and allied health disciplines. Response rates for feedback were 80% (n = 20), 43% (n = 10), and 45% (n = 11). Fifty percent (n = 21) reported high satisfaction, 41% (n = 16) moderate, and 7% (n = 3) low. Participants noted shifts in their perceptions, recognizing professionalism as a learned skill rather than an inherent trait. Key takeaways included the significance of effective communication, empathy, and resilience in shaping professional identity. In terms of educational impact, participants intended to model professionalism, reinforce positive behaviors, and explicitly integrate PIF into their teaching. Proposed strategies included experiential learning, structured orientation, and active learning methods. The workshop was appreciated for its interactive elements, such as group discussions, case-based learning, and open forums. However, areas for improvement included better time management, concise delivery, enhanced multimedia use, and more structured engagement. Participants also suggested extending the workshop to resident doctors and a mixed audience of residents and consultants.ConclusionThe workshop effectively conveyed professionalism and PIF concepts. Future iterations could benefit from refinements in structure and delivery, as well as audience expansion. Our experience may guide similar faculty development initiatives in other healthcare institutions.